Organochlorine Contaminants in the Country Food Diet of the Belcher Island Inuit, Northwest Territories, Canada - Cameron, Marjorie; Weis, I. Michael (ARCTIC, 1993)
An initial assessment of the country food diet at the Belcher Islands' community of Sanikiluaq, Northwest Territories, was made by interviewing 16 families during May-July 1989. Estimates of consumption per day were established over a two-week period for 10 of these families. This information was utilized along with previously published harvest data for the community to estimate country food consumption in grams/day and kg/year. Beluga (Delphinapterus leucas), ringed seal (Phoca hispida), arctic charr (Salvelinus alpinus), common eider (Somateria mollissima) and Canada Goose (Branta canadensis) were found to be important components in the diet during this period. Results of analysis for organochlorine contaminants reveal that ringed seal fat and beluga muktuk (skin and fat layer) samples have the highest concentration of DDE and total PCBs among the country food species. Average DDE and total PCB values were 1504.6 micro g/kg and 1283.4 micro g/kg respectively in ringed seal fat and 184.3 micro g/kg and 144.7 micro g/kg respectively in beluga muktuk. Comparison of contaminants in seal fat indicates concentrations approximately two times higher in samples from the Belcher Islands than from sites in the Canadian Western Arctic, but lower than concentrations reported from various European sites. The daily consumption estimates in grams/day were used along with organic contaminant analysis data to calculate the estimated intake levels of 0.22 micro g/kg body weight/day of total DDT and 0.15 micro g/kg body weight/day of total PCBs during the study period. Although limited in sample size, studies such as this provide a framework from which to establish future consumption guidelines more applicable to arctic systems and native diets.Key words: organic contaminants, PCBs, DDE and total DDT, Inuit diet, Belcher Islands On a procédé à une première évaluation de l'alimentation fournie par la nature dans la communauté de Sanikiluaq des îles Belcher dans les Territoires du Nord-Ouest, en interviewant 16 familles de mai à ...